A quantitative and molecular examination of Tuber melanosporum mycorrhizae in Quercus ilex seedlings from different suppliers in Spain - Alvarado, P.; Manjon, J. L. (FOREST SYSTEMS, 2013)
Aim of study: The aim of the work was to determine the degree of mycorrhization of Quercus ilex L. subsp. ballota (Desf.) Samp. by the black truffle fungus T. melanosporum Vittad. by quantitative and molecular analyses. Area of study: seedlings inoculated by different Spanish suppliers. Material and methods: The internal transcribed spacers (ITS) of mycorrhizae from different plants were amplified by nested PCR involving fluorescently-labelled primers, and the amplicons either directly sized by ARISA or analysed by TRFLP following their digestion with restriction endonucleases. TRFLP analysis distinguished between mycorrhizae of T melanosporum, T. indicum Cooke & Massee and T. borchii Vittad., as suggested possible by virtual (in silico) TRFLP analysis and real TRFLP analysis of the ascomata of these species. Main results: Significant differences between suppliers were detected in terms of the mean number of mycorrhizae established per plant and percentage mycorrhization. These results allowed the following quality standards for 2 year-old plants to be proposed: a) good quality: >3,000 mycorrhizae/plant, >40% mycorrhization, b) medium (acceptable): >3,000 mycorrhizae/plant, >30% mycorrhization, c) low quality: <3,000 mycorrhizae/plant or <30% mycorrhization, always supposing the mycorrhizae counted represent the species of interest as confirmed by the presence of its DNA and the absence of DNA belonging to contaminating species. Finally, a new microsatellite allelic map obtained from the analysis of several T melanosporum populations across Spain was used to provide a tool capable of determining the geographic origin of the fungi used to inoculate plants. Research highlights: The proposed quality standards can be useful for the evaluation and certification of commercialized Q. ilex plants mycorrhized with T. melanosporum.
The following values have no corresponding Zotero field: pub-location: CTRA CORUNA KM 7 5, MADRID, 28040, SPAIN publisher: INST NACIONAL INVESTIGACION TECHNOLOGIA AGRARIA ALIMENTARIA
Keywords: Certification; fungi; mycorrhiza; TRFLP; truffle

Effect of Sphaerosporella brunnea mycorrhizas on mycorrhization of Quercus ilex × Tuber melanosporum - Garcia-Montero, L. G.; Massimo, G. Di; Manjon, J. L.; García‐Cañete, J. (New Zealand Journal of Crop and Horticultural Science, 2008)
Abstract It is generally accepted that Sphaerosporella brunnea is a significant ectomycorrhizal contaminant in nurseries producing plants mycorrhized with various species of Tuber, and subsequently in truffières after outplanting. At the University of Alcalá, Spain, 397 small plants of Quercus ilex which were mycorrhized with Tuber melanosporum were inadvertently contaminated with S. brunnea, and this contamination was then monitored for 2 years. Sixty percent of the plants were contaminated and had S. brunnea ascomata on the surface of the container on one or several occasions. However, a Spearman test provided no evidence that S. brunnea mycorrhizas affected T. melanosporum mycorrhization whereas other contaminating ectomycorrhizal fungi significantly did. Therefore, it appears that S. brunnea is not detrimental to plants which are well mycorrhized with T. melanosporum.
doi: 10.1080/01140670809510231doi: 10.1080/01140670809510231The following values have no corresponding Zotero field: publisher: Taylor & Francis
Keywords: Black truffle; Mediterranean mushroom; Mycorrhizal fungi; mycorrhized contamination; Tuber melanosporum